Me and My Behavior: An Experiment on Individual Characteristics and Compliance Behavior in Recreational Fishing - Mackay, Mary; van Putten, Elizabeth Ingrid; Yamazaki, Satoshi; Jennings, Sarah; Sibly, Hugh (Frontiers in Marine Science, 2020)
Non-compliance with regulations is a complex problem in recreational fisheries management, having the potential to evoke uncertainty for conservation and socio-ecological outcomes and to undermine management efforts. While we know that in fisheries people make trade-offs between following or breaking rules, it is of interest to determine how people respond to different management incentives to curtail non-compliance. The overall aim of this study is to examine what individual psycho-social characteristics are associated with responses to instrumental and normative management incentives in a recreational fisheries context through the use of an economic experiment. We examined five psycho-social characteristics, three of which (expectation of behavior of others, social norms, and risk preferences) have separately been explored within the fisheries compliance literature, while two factors (ecological values and personality types) have yet to be explored. While information about these two latter characteristics is limited within the fisheries compliance literature, our results suggest that they are relevant predictors for certain compliance groups across compliance incentives. The findings underline that there is significant heterogeneity in the associations between psycho-social make-up and compliance behaviors. Knowledge of this behavioral relationship can progress fisheries management toward increased innovation by encouraging the management of the individual fisher rather than the average fisher.